Some Generalizations of Weak Cyclic Compatible Contractions: P. Sumati Kumari, Jamnian Nantadilok, Muhammad Sarwar - Team, Support (Thai Journal of Mathematics, 2019)
In this paper, we establish the existence theorems for weak cyclic compatible contractions and cyclic compatible Mk-contractions. Our results extend and improve existing known results in [15] as well as other results in the literature. We provide examples to illustrate and support our main results.